INVESTMENT PAYOFFS OF TOP ESG PORTFOLIOS IN THREE-LARGEST ASIA’S COUNTRIES - Christiani, Maria; Ekawati, Erni (Jurnal Akuntansi Kontemporer, 2025)
Research Purposes. The purposes of the study are to evaluate the performance of the top Environment Social and Governance (ESG) portfolios in the three largest economies and most populous countries in Asia: Indonesia, China, and India, and to capture the dynamics and payoffs of socially responsible investing (SRI) in these markets. Research Methods. The Top ESG portfolios for each country are formed by the 30 firms with the top ESG scores listed on their respective stock exchanges from 2016 to 2022, and their performance is evaluated using the five-factor Capital Asset Pricing Model (CAPM), with a Brown portfolio of firms with no ESG scores from high-sensitive industries serving as a benchmark. Research Results and Findings. The research results indicate that the Brown portfolio consistently generates abnormal returns in three countries, indicating a high level of risk, while the abnormal returns for the Top ESG portfolio vary: none were found in Indonesia and China, but they are significant in India. The findings imply that high ESG scores provide high legitimacy in the market that could drive the stock price up, and eventually benefiting SRIs through financial rewards.